PENGEMBANGAN PANDUAN KOMPETENSI MULTIKULTURAL BERBASIS NILAI MODERASI AN-NAHDLIYAH BAGI CALON KONSELOR - Sa'idah, Ishlakhatus (LP2M IAI Miftahul Ulum Pamekasan, 2022)
The concept of multicultural competence of counselors is dominated by Western theories which are loaded with value content so that in practice they often encounter obstacles. Therefore, adaptation efforts are needed into the Indonesian context by taking into account socio-cultural and religious values. The purpose of this study is to develop multicultural skills for prospective counselors who meet the criteria, accuracy, accuracy, and propriety that have been tested by experts and user tests. In addition, the guide can be used in the development of multicultural skills of prospective counselors. This research uses development research design. The results showed that the multicultural competency guide was based on the value of moderation and met the criteria, accuracy, accuracy, and appropriateness. Based on the results of the pre-test and post-test, it shows that there is a significant difference between before and before being given a multicultural competency guide based on an-Nahdliyah moderation values. This is evidenced by the difference in the mean at the time of the pre test with the difference in the mean at the time of the post test and also from the results of the Paired Sample T Test which shows that the value of Sig (2-tailed) is 0.000.